Assessment of Saltwater Crocodiles along Bako River during Three Monsoon Seasons - Ahmad Azreen, bin Azizan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Saltwater crocodile, Crocodylus porosus is a large, cold-blooded, amphibious reptile inhabiting the estuarine rivers and coastal areas of Sarawak, including Bako River, north of Kuching. This study aims to (i) determine the relative density of C. porosus during the southwest monsoon (SWM), inter-monsoon (IM) and northeast monsoon (NEM), and (ii) examine the relationship between C. porosus densities with selected insitu water quality parameters and total rainfalls. By using the night spotting technique, surveys on C. porosus population were carried out in Bako River during SWM, IM and NEM. The highest relative density was recorded during NEM (4.87 non-hatchling/km), followed by SWM (3.60 non-hatchling/km) and IM (1.93 non-hatchling/km). Seasonal fluctuations on the number of crocodiles according to different cohorts were most probably due to several reasons including breeding biology, nesting behaviour, level of wariness, moonlight and thermoregulation behaviour. Seasonal rainfall data shows that C. porosus densities had an inverse relationship with the total rainfalls. Selected in-situ water quality parameters result suggests that C. porosus densities had a subtle relationship with the salinity, temperature and pH.